Ralstonia solanacearum type III effector RipAA targets chloroplastic AtpB to modulate an incompatible interaction on Nicotiana benthamiana - Miao, Yangchen; Wu, Leilei; Xue, Qi; Zhang, Qiuyan; Zou, Huasong (Frontiers in Microbiology, 2023)
The type III effector RipAA of Ralstonia solanacearum GMI1000 plays a critical role in the incompatible interaction on Nicotiana benthamiana. In this study, we report that RipAA induced the accumulation of hydrogen peroxide (H2O2) and genome DNA degradation in N. benthamiana, which were accompanied by a hypersensitive reaction. Simultaneously, the marker genes for salicylic acid (SA) signaling were induced and those for jasmonic acid (JA) signaling were reduced. N. benthamiana chloroplastic AtpB, the ATPase β subunit, was identified as an interactor with RipAA. The silencing of atpB in N. benthamiana resulted in the inability of RipAA to induce a hypersensitive response, a compatible interaction with GMI1000, and an enhanced sensitivity to bacterial wilt. Taken together, our data support the concept that RipAA determines host-range specificity by targeting the host chloroplastic AtpB.